The Readiness of Digital Bureaucracy in the Transformation of Public Services in Sorong City Is Reviewed from the Capacity and Digital Literacy of ASN - Ani Aksa Maniani; Karmanis Karmanis; Try Lestari Hadiati (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the readiness of the digital bureaucracy in transforming public services in Sorong City, focusing on the capacity and digital literacy of the State Civil Apparatus (ASN). The research uses a mixed-methods approach with a sequential explanatory design, in which quantitative data are collected through questionnaires and analyzed descriptively and correlatively, and then deepened with qualitative data through in-depth interviews. The study's results show that the Sorong City Government's digital bureaucracy is in the early stages of implementation and has not been optimal. ASN capacity and ASN digital literacy are positively related to the readiness of the digital bureaucracy, but they remain at a sufficient, fundamental level. The transformation of digital public services has increased the efficiency of certain services. However, this improvement has not been evenly distributed due to limited human resources, system integration challenges, and a bureaucratic work culture. The study's implications emphasize the importance of strengthening civil servants' capacity and digital literacy as a prerequisite for the successful transformation of digital public services. The limitation of this study is in use of correlation analysis, which does not explain causal relationships. Further research is recommended to use a more comprehensive analytical approach and expand the scope of the research area.